Leishmaniose visceral e o sistema nervoso central: inflamação nas infecções natural canina e experimental em camundongos: Guilherme Dias de Melo. - - Melo, Guilherme Dias de [UNESP] (2015)
Visceral leishmaniasis is an important parasitic disease, with worldwide distributions that affects humans and animals. There are reports of brain involvement during the infection; however, its pathogenesis has not been completely elucidated. Therefore, with this study, we aimed the evaluation of the inflammatory response in the brain and the integrity of the blood-brain barrier in naturally infected dogs, and the establishment of an experimental mice model that could allow the evaluation of the infection dynamics, as well as the localization of the parasite and the inflammatory response in vivo. Naturally infected dogs presented a specific chemokine profile in the brain, highly attractive to T-lymphocytes, besides the evident blood-brain barrier disruption, with increased albumin quota and elevated concentrations of anti-Leishmania antibodies in the cerebrospinal fluid. Using molecular techniques and state-of-the-art in vivo imaging tools, we could determine the presence of parasites in the brain of experimentally infected Balb/c mice, as well as its intracranial localization. Brain inflammation, evaluated during four months post-infection, presented two distinct phases, one acute phase in the first fourteen days, and one phase of re-inflammation after three months of infection. Altogether, the data from this study allow us to confirm that the brain is affected during visceral leishmaniasis, and reinforce the fact that the brain involvement has been neglected during visceral leishmaniasis